John Eggleston Memorial Lecture Models of change: The future of design education - Baynes, Ken (Design and Technology Education: An International Journal, 2010)
This paper discusses design and design education in the context of four major social and environmental concerns identified by Bruce Archer in 1973: overpopulation; pollution; depletion of natural resources; control. It argues for the social and economic importance of design education in primary and secondary schools. It identifies ‘designerly thinking’ as an aspect of cognitive modelling directed towards imagining viable alternative futures. The paper then reviews the potential of design educational activity, focusing on seven themes: • The aims of design education. • The significance of practical education. • Encouraging the imagination. • The creative value of aesthetic awareness. • The value of learning through making. • The creative relationships between designing and making. • The educational purpose of doing design projects. Research agenda are identified in key areas: the nature of imaginative activity and its significance in education; graphicacy and cognitive modelling in design.